Construction of Modified Carbon Paste Electrode for Highly Sensitive Simultaneous Electrochemical Determination of Trace Amounts of Copper (II) and Cadmium (II). Issue 2 (23rd July 2015) - Afkhami, Abbas; Soltani‐Shahrivar, Morteza; Ghaedi, Hamed; Madrakian, Tayyebeh
Abstract: A chemically modified electrode was constructed for rapid, simple, accurate, selective and highly sensitive simultaneous determination of Cu(II) and Cd(II) using square wave anodic stripping voltammetry. The electrode was prepared by incorporation of SiO2 nanoparticles, coated with a newly synthesized Schiff base, in carbon paste electrode. The limit of detection was found to be 0.28 ng mL −1 and 0.54 ng mL −1 for Cu(II) and Cd(II), respectively. The proposed chemically modified electrode was used for the determination of copper and cadmium in several foodstuffs and water samples. Abstract :